(untitled) (Research, Society and Development, 2022)
Jaundice is the increase in bilirubin in the newborn’s blood, in some cases, if untreated, it can cause irreversible sequelae, in addition, information about clinical signs, diagnosis, treatment and assistance to the NB are essential for directing the care provided. by the nursing professional. Therefore, the present study aims to describe, through a literature review, the care provided by nurses to newborns with jaundice. Therefore, this review sought to analyze scientific articles published between 2015 and 2021, using keys. The selected articles went through a process of inclusion and exclusion, later, the selected ones were organized and described in a table. In total, 74 articles were analyzed, of these 12 manuscripts were selected, as they describe the main clinical signs of newborns with jaundice, the tests to quantify the concentration of bilirubin in the blood, the treatments performed to the newborns and the actions that the nursing professional must provide, from the reception to the evolution of the NB with jaundice in the treatment. Therefore, the information collected in this study is important to direct the assistance provided by the nursing professional to the NB with jaundice with the aim of promoting health.